Cytotoxic, apoptotic, and anti-inflammatory properties of Adenoon indicum leaf methanolic extract using HT29 cell lines - Patil, Ajit B.; Shinde, Anilkumar J. (Bangladesh Journal of Pharmacology, 2025)
In the present study, methanolic extract of Adenoon indicum leaves is investigated for its cytotoxic, apoptotic, and anti-inflammatory properties using HT29 cell lines. The extract yield was 1.6%. MTT assay of HT-29 cells shows that the extract's IC50 value was 80 μg/mL with 10 μg/mL for doxorubicin, confirming its cytotoxic effect. Flow cytometry analysis demonstrated that extract caused cell cycle arrest, with 2.3% of cells in the G2/M phase and 32.2% in the S phase at a dosage of 160 μg/mL. Propidium iodide/annexin V staining revealed that the extract caused 3.1% early apoptosis and 6.0% late apoptosis, compared to 0% early apoptosis and 13.4% late apoptosis with doxorubicin at 11 μg/mL and anti-inflammatory effect in the egg albumin denaturation inhibition assay. The results show methanolic extract of A. indicum has anti-cancer activities against colorectal cancer via triggering apoptosis, and cell cycle arrest. In addition, it has an anti-inflammatory effect.